Community guidelines to increase the reusability of marine microfossil assemblage data - Jonkers, Lukas (2025)
Data on marine microfossil assemblage composition has multiple applications. Initially, it was primarily used for (chrono)stratigraphy and palaeoecology, but these data are now also widely used to study evolutionary and ecological processes, such as past biodiversity and its links with environmental dynamics, or to provide a basis for conservation efforts and biomonitoring. The large range of potential applications renders microfossil abundance data ideal for reuse. However, the complexity inherent in taxonomic data, which encompass extant and extinct species, coupled with the inherent intricacies of information on biological communities extracted from sedimentary archives, poses considerable hurdles in reusing marine microfossil data, even when it is publicly available. Here, we present guidelines derived from an online survey conducted within the marine micropalaeontological community, aimed at improving the reusability of microfossil assemblage data. These guidelines advocate for clarity and transparency in the documentation of the methods and the outcome, and we outline the data attributes required for effective reuse of micropalaeontological data. These guidelines are intended for researchers who generate microfossil abundance datasets, as well as for reviewers, editors, and data curators at repositories.One hundred and thirteen researchers evaluated the relevance of about 50 data attributes that might be needed to enable and maximise the reuse of marine microfossil abundance datasets. Each property is ranked based on the survey results. All information is, in principle, considered “desired”. Information that improves the reusability is ranked as “recommended”, and information that is required for reuse is ranked as “essential”. Analysis of a selection of datasets available online reveals a rather large gap between data properties deemed essential by survey participants and what is actually contained in publicly available microfossil assemblage datasets. Whereas the survey indicates that the micropalaeontological community values good data stewardship, improving data reusability still requires new efforts to incorporate all the essential information. The guidelines presented here are intended as a step in that direction. Determining the optimal forms and formats for data sharing are obvious next steps the community needs to take.